2020
DOI: 10.1101/2020.09.29.20202846
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 antibody responses in patients with aggressive haematological malignancies

Abstract: The development of antibody responses to SARS-CoV-2 is an indicator of seroprevalence and may afford protection from infection. It has been presumed that antibody responses to SARS-CoV-2 will be impaired in patients with aggressive haematological malignancy (PHM) due to underlying immunological dysfunction caused by malignancy or systemic anti-cancer treatment (SACT), placing them at increased risk. Here we analysed longitudinal serum samples from ten hospitalised PHM with aggressive disease and on SACT, colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 19 publications
(53 reference statements)
3
10
0
Order By: Relevance
“…Analysis of antibody responses in cancer patients and HV with SARS-CoV-2 infection revealed comparable positivity rates as well as antibody ratios and titers. This is in line with recent ndings in CLL and AML patients (16,17), indicative of functional humoral SARS-CoV-2 immunity in these patients. Similar to previous reports in non-cancer COVID-19 patients (25)(26)(27), a trend to increased anti-S1 IgG ratios was observed in cancer patients with a more severe course of COVID-19.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Analysis of antibody responses in cancer patients and HV with SARS-CoV-2 infection revealed comparable positivity rates as well as antibody ratios and titers. This is in line with recent ndings in CLL and AML patients (16,17), indicative of functional humoral SARS-CoV-2 immunity in these patients. Similar to previous reports in non-cancer COVID-19 patients (25)(26)(27), a trend to increased anti-S1 IgG ratios was observed in cancer patients with a more severe course of COVID-19.…”
Section: Discussionsupporting
confidence: 92%
“…As of now, data on immune responses and immunity to SARS-CoV-2 in cancer patients are very limited. Two recent studies reported IgG antibody responses in 88% and 67% in acute myeloid leukemia (AML) and chronic lymphocytic leukemia (CLL) patients suffering from COVID-19, respectively (16,17). To date, no data are available on SARS-CoV-2-directed T cell responses in cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…ELISA was used to screen plasma samples for antibodies against the external Spike antigen, using immobilized recombinant Spike S1 1-530 subunit protein (S1), and against immobilized full-length internal Nucleoprotein (N) antigen to confirm prior infection as previously described (Ng et al 2020; O’Nions et al 2021; Pickering et al 2020) ( Fig. 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…S1A, B ) and as previously described (Pickering et al 2020). The screening assay, followed by titer quantification (based on an in-assay standard curve) (O’Nions et al 2021), demonstrated that 95.8% (23/24) of individuals from the HIV positive group with prior laboratory confirmed COVID-19 and 30.43% (7/23) with suspected disease, during the first wave of the pandemic, had measurable titers for SARS-CoV-2 S1 and N sampled at a median 146 DPSO (DPSO range 46-232) and 181 DPSO (range 131-228), respectively ( Fig. 1A-C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation